Agents of subversion : the fate of John T. Downey and the CIA's covert war in China - Delury, John (Cornell University Press, 2022)
"This book explores the covert side of US-China relations during the Cold War and subversion-repression dynamics in both countries. It documents CIA efforts to subvert Mao Zedong's Communist Party rule by recruiting a Third Force during the Korean War, and examines the subsequent two decades of diplomatic standoff, especially over the case of captured secret agent Jack Downey"--